Roles for chloride ion and fibrinogen in the activation of [Glu1]plasminogen in human plasma. - Gaffney, P J (1988)
Using two-dimensional immunoelectrophoresis and an antibody to alpha 2-antiplasmin, we assessed the plasmin generated in serum under different conditions as the plasmin-alpha 2-antiplasmin complex. Activation in serum of human [Glu1]plasminogen ([Glu1]Pg) by recombinant tissue plasminogen activator was inhibited by the normal serum levels of Cl- and was enhanced by physiological levels of fibrinogen in the presence or absence of Cl-. These results agree with the recognized ability of Cl- to induce a conformation in [Glu1]Pg less favorable for its activation than the conformation that results without Cl-. The enhancing effect of fibrinogen surpassed the inhibitory effect of Cl- over a wide range of recombinant tissue plasminogen activator concentrations in physiological serum. Lesser inhibition by Cl- was seen in a purified clot-lysis system, suggesting that [Glu1]Pg conformation when attached to soluble fibrin matrix was less affected by the anion. The data regarding the roles of circulating fibrinogen and Cl- in controlling the plasma level of activated [Glu1]Pg have important implications in thrombolytic therapy with recombinant tissue plasminogen activator.